2015
DOI: 10.5505/phd.2015.18189
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Effects of Exposure to Violence and Affecting Factors on Job Satisfaction of Emergency Nurses

Abstract: ÖZETAmaç: Araştırma acil serviste çalışan hemşirelerin şiddete maruz kalma ve iş doyumuna etkili olan faktörlerin incelenmesi amacıyla yapıldı. Gereç ve Yöntem:Araştırma Ankara'nın Yenimahalle ilçesinde altı hastanenin acil servislerinde çalışan 128 gönüllü hemşire ile yürütül-dü. Araştırmamız 15 Ocak-15Mart 2014 tarihleri arasında tanımlayıcı türde bir araştırma olarak yapıldı. Araştırmanın verileri gönüllülerin şiddet ve iş doyumuna ilişkin özelliklerini tanımlayan anket formu ve Minnesota İş Doyum Ölçeği il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Our study revealed that nurses were exposed to violence both before and during the pandemic and that the most common type of violence was verbalemotional-psychological violence. Studies conducted in Turkey reported that 68% of the nurses were subjected to verbal violence and 33.6% to threat/psychological violence (Bahar et al, 2015), 60.8% of the nurses working in emergency departments, intensive care units, and psychiatry clinics were subjected to verbal or physical violence (Ünsal Atan et al, 2013), and 78.3% of the nurses experienced verbal violence (Çuvadar & Ekuklu, 2020). Our study is similar to the literature regarding the type of violence that nurses are frequently exposed to.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study revealed that nurses were exposed to violence both before and during the pandemic and that the most common type of violence was verbalemotional-psychological violence. Studies conducted in Turkey reported that 68% of the nurses were subjected to verbal violence and 33.6% to threat/psychological violence (Bahar et al, 2015), 60.8% of the nurses working in emergency departments, intensive care units, and psychiatry clinics were subjected to verbal or physical violence (Ünsal Atan et al, 2013), and 78.3% of the nurses experienced verbal violence (Çuvadar & Ekuklu, 2020). Our study is similar to the literature regarding the type of violence that nurses are frequently exposed to.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, nurses reported that they were exposed to physical and verbal-emotional-psychological violence most often by patients' relatives and to sexual violence most frequently by patients before and during the pandemic. According to studies conducted in Turkey, 60.2% of the nurses were subjected to violence by patient relatives, and 33.6% by patients (Bahar et al, 2015), and 44.3% of the violence was found to come from patient relatives (Çuvadar & Ekuklu, 2020). Our study results are similar to those of the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the studies in the literature with similar findings, it was found that the job motivations of the nurses were moderate level or below average 24 - 28…”
Section: Discussionmentioning
confidence: 84%
“…Bahar et al also found that nurses working continuous day shifts experienced higher job satisfaction. 29 The Turkish Nurses Association (TNA), in its report on the working conditions of nurses, stated that working long shifts with constantly changing hours adversely affects nurses' circadian rhythms, as well as the quality of patient care, safety, and their family and social life. 30 Similarly, the International Labor Organization (ILO) reported in 2016 that one of the most significant stressors for nurses related to their working environment is the shift and on-call working system.…”
Section: Discussionmentioning
confidence: 99%